Mappacci Interconnection in Bugis Tradition and Strengthening of Pangadereng (Ethics) - Yunus Salik; Kamaruddin Mustamin (Jurnal Hikmatuna, 2022)
The purpose of the study illustrates that marriage contains good social values in character education. Ethnographic method is the research of the culture of a community. Ethnographic research involves extensive observations of the Bugis community in Tana Luwu, most often through participant observation, where researchers immersed in the daily lives of the community and observed and interviewed participants in the group. Bugis wedding ceremony in the implementation of mappacci or tudampenni means cleanliness of the body and sanctity of the soul. The value of sacredness is clearly seen from the implementation of various special rituals such as bathing refuse bala, reading barzanji things is the value of respect for women. On the other hand, community marriage has character values such as help; It is clearly a social value embodied in this tradition. The concept of help cannot be separated from the principle of gotong royong. Solidarity; The value of solidarity cannot be separated from this tradition. What's more, there has been a value that is maintained in this tradition, namely gotong royong and please help. Communicative; It is one of the most important parts of this tradition, because if there is no communication in any case, then it is very impossible that stage by stage of the implementation of the mappanre temme' tradition will be carried out. Ethics in Bugis culture can strengthen pangedereng (customs) and connect with each other.